Analisis Komposit Dengan Penguat Serat Rami 40% Dan Serbuk Kayu Sengon 60% Pada Fraksi Volume 40%,50%,60% Bermatrik Resin Polyester Untuk Panel Akuistik - Pradika, Leody Ilham, Wijianto, ST, M.Eng, Sc, Joko Sedyono, ST, M.Eng, Ph.D (2016)
ABSTRACT Purpose of the research is to know tensile strength, bending strength, sound absorption and to describe macro photographs of results of tensile and bending strengths of composite strengthened with boehmeria nivea and sengon sawdust with polyester resin matrix at volume fractions of 40%, 50% and 60%. The composite is made from mixing of boehmeria nivea and sengon sawdust with matrix of polyester resin. The specimen was made by using Hand Lay-up method with ratio of 40% boehmeria nivea and 60% sengon sawdust using polyester resin BQTN-EX157. Process of the testing was tensile strength, bending strength and sound absorption. Result of tensile strength showed that the greater volume fraction, the greater tensile strength. The maximum tensile strength of 36.097 N/mm2 was found at volume fraction of 60% and the minimum one of 24.03 N/mm2 was found at volume fraction of 40%. Results of bending strength test indicated that the increased volume fraction, the increased bending strength. Maximum bending strength of 75.170 Mpa was found at volume fraction of 60% and the lowest one of 49.750 was found at volume fraction of 40%. Results of sound absorption test obtained that the increased volume fraction, the increased absorption of sound. The highest sound absorption of 1.94 dB was found at volume fraction of 60% and the lowest one of 1.32 dB was found at volume fraction of 40%. The macro photograph of tensile and bending strengths testing showed the composite specimen had fluctuated and unordered fragment. Void enlargement and pull-out of the fiber highly predominated at volume fractions of 40%, 50% and 60%. Keywords: Boehmeria Nivea fiber, Polyester Resin BQTN - EX 157, Volume Fraction